European Support for The Agri-Food Processing Sector in Romania - Alecsandra PARNUS; Raluca MITULESCU; Eliza GHEORGHE; Florentina CONSTANTIN (Communications of International Proceedings, 2021)
Globally, it is estimated that food and agricultural systems in line with sustainable development goals would provide nutritious and affordable food to the growing world population, contribute to the restoration of vital ecosystems and could create a new economic value, over € 1.8 trillion by 2030 (Business & Sustainable Development Commission, 2017). European food products represent the standard of safe and nutritious food worldwide, which determines Europe to aim to draw new strategies for sustainable growth, ensuring the protection of resources but also designed to stimulate and improve the quality of life of the population. Likewise, the food system must be strong and resilient to exceptional situations such as the COVID-19 pandemic, so that its functionality is not adversely affected, to ensure access to sufficient supply at reasonable prices, but also safe and efficient to guarantee the safety of the population's health.
Keywords: Processing; sustainability; processing units; optimization of production operations; expansion of product categories; food chain; non-reimbursable financing.